THE INFLUENCE OF SPEED, AGILITY, COORDINATION OF FOOT, BALANCE AND MOTIVATION ON SKILL OF PLAYING FOOTBALL - Ahmad Adil; James Tangkudung; Achmad Sofyan Hanif (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This research uses survey method to see the influence between variables. Technique of data analysis using path analysis (path analysis). Path analysis technique is used to test the direct and indirect influence on speed, agility, coordination, balance and motivation to the playing skill of soccer student of Faculty of Sport Science Makassar public university. Technique of path analysis with SPSS program version 20.00 at significance level Î± = 0.05. The results of this study are as follows: (1) There is a positive influence of 0.612 between the speed of soccer playing skills and contributing 37.4% (2) There is a positive influence of 0.687 between agility to the skills of playing football and contribute 47.1% (3) There is a positive influence of 0.862 between eye-foot coordination of soccer playing skills and contributes 74.3% (4) There is a positive influence of 0.636 between the balance of soccer playing skills and contributes 40.4% (5) positive is 0.816 between motivation to soccer playing skill and contribute 66,6% (6) There is positive influence equal to 0,531 between speed to motivation and contribute equal to 28,2% (7) There is positive influence equal to 0,621 between agility to motivation and contribute equal to 38.6% (8) There is a positive influence of 0.743 anta (9) There is a positive influence of 0,564 between the balance of motivation and contribution of 31.8% (10) There is a positive influence of 0.824 between the speed of the skills of playing football through motivation and contributing 66.8% (11) There is a positive influence of 0.879 between agility of soccer playing skills through motivation and contributing 67.3% (12) There is a positive influence of 1.344 between foot-toe coordination of soccer playing skills through motivation and contributing 67 , 2% (13) There is a positive influence of 0.878 between the balance of soccer playing skills through motivation and contribute 67.0%. Keywords: Speed, agility, coordination, balance, motivation and the skills of playing football.